THE ROLE OF SMART FARMING 5.0 IN CREATING FOOD SOVEIREGNTY IN INDONESIA - Riswandi, D. Iwan; Safruddin, Safruddin; Suryaningrum, Dyah; Antesty, Sella; Hamidah, Emmy (ITB AAS Indonesia Surakarta, 2024)
Abstract As we know, Indonesia is an agricultural country whose main income comes from the agricultural sector. Indonesia's position in the equatorial region and tropical climate makes Indonesia a country with megabiodiversity. Indonesia has a variety of regional conditions with agricultural management techniques according to the needs of farmers in the region. Smart farming 5.0 which utilizes artificial intelligence has become a mainstay for the Indonesian Government in the current digital era. Smart farming 5.0 can encourage farmers' work so that agricultural cultivation becomes measurable and integrated. Farmers can cultivate without depending on the season but through mechanization. The planting to harvesting process can be carried out accurately starting from labor, planting time and the harvesting process. Several smart farming technologies such as blockchain which can make it easier to track the supply of agricultural products for modern off-farm farming, agri drone sprayer (drone spraying pesticides and liquid fertilizer), drone surveillance (drones for mapping land), soil and weather sensors (soil and weather sensors) , smart irrigation system (smart irrigation), Agriculture War Room (AWR), Siscrop (information system) which have been implemented in several areas. The varying levels of education of farmers, the phenomenon of aging farmers, the high cost of Smart Farming technology tools are the biggest obstacles for farmers in implementing Smart Farming. This article aims to analyze the magnitude of the role of Smart Farming 5.0 to utilize the potential of millennial farmers as actors and analyze various government policies to support the implementation of Smart Farming 5.0 as an effort to create Indonesian food sovereignty. Keywords: Smart Farming 5.0., Food Sovereignty, Agriculture